ANALYSIS OF FINANCIAL INCLUSION INDICATORS FOR THE IRAQI BANKING SECTOR FOR THE PERIOD (2009-2022) (World Economics and Finance Bulletin, 2024)
The study aimed to analyze financial inclusion indicators for the Iraqi banking sector for the period from (2009 - 2022) and to know the concepts of financial inclusion, as well as to analyze the relationship between financial inclusion indicators. To achieve the objectives of this study, financial inclusion indicators were analyzed for the Iraqi banking sector represented by the Central Bank of Iraq for the period from (2009 – 2022) As financial inclusion has become one of the main goals that financial institutions seek to achieve, including the Central Bank of Iraq, by developing a strategy to enhance financial inclusion in Iraq, the results revealed the weakness of financial inclusion indicators in Iraq and a clear decline in the values of its backward indicators, which confirms the need In order to enhance these indicators and deliver them to the largest possible number of the population, financial inclusion can be a goal for the Central Bank through which it seeks to deliver financial services to all segments of society, especially the deprived and poor segments.
Keywords: Financial inclusion; demographic status of Iraq; Banking depth